Strategi Komunikasi Pengelola Hotel Mutiara Syariah Bukittinggi Dalam Melayani Tamu - Dinda Rahmadani Putri; Tomi Hendra (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2023)
The development of the hotel business is currently very rapid in Indonesia. So communication has become an important part in hotel companies as a medium for companies whose targets are guests. As time goes by, sharia principles have entered the hotel business. This is what makes researchers interested in analyzing what kind of management communication strategies are used by the Mutiara Syariah Bukittinggi Hotel which uses sharia principles in serving guests. This research aims to determine the communication strategy of Mutiara Syariah Bukittinggi Hotel Managers in serving guests. This research uses a descriptive method with a qualitative approach. The subject of this research is the Mutiara Syariah Bukittinggi Hotel Manager and the object is the communication strategy of the Mutiara Syariah Bukittinggi Hotel Manager in serving guests. Meanwhile, in collecting data in this research, researchers collected data from observation, interviews and documentation. Based on the results of research with the Mutiara Syariah Hotel Bukittinggi, the strategy for serving guests is first, the manager makes a plan as to what kind of communication strategy will be used to serve guests of the Mutiara Syariah Hotel Bukittinggi. Second, employees carry out communication strategies as planned by the management of the Mutiara Syariah Bukittinggi Hotel. Third, the manager looks at the results of the communication strategy in serving guests, whether the communication strategy implemented is good or not. Fourth, the management of the Mutiara Syariah Hotel Bukittinggi reports every activity carried out to the leadership regarding communication strategies in serving guests of the Mutiara Syariah Hotel Bukittinggi.